The concept of community disaster resilience: a proposed mixed method study on "the adaptation of Australian community disaster resilience scorecard & self-assessment of Community Disaster Resilience (CDR) - Mohamed Ludin, Salizar; Firdaus, Mohd Khairul Zul Hasymi; Arbon, Paul (2015)
Introduction: Community resilience is the sustained ability of a community to withstand and recover from adversity after an emergency. In preparation for the post-2015 Hyogo framework for action, countries across the globe emphasizes supports to the local governments and community organizations in implementing community resilience programs (HFA 2013). Thus Public health nursing had the opportunity to increase the capacity across the disaster cycle and remain constant in the national planning framework on disaster. Problem statement: Malaysian government has outlined the need to re-look and develop the country's sustainable disaster recovery policies and rebuilding post-disaster. Nevertheless, the level and how to measure our community disaster resilience is unknown. Objectives: This research aim to adapt the Australian-Torrens Resilience Institute (TRI) community disaster resilience scorecard and have the basis of knowledge on Malaysian community disaster resilience and views on the prevention, preparedness, response and recovery paradigm. Methods: A mixed method study in plan through discussion and adaptation of the community disaster scorecard and survey in the six highest flood affected community area/district. The estimated sample size for the survey is 384 (5% margin of error, confident interval of 95%). Expected outcome: The finding will assist in keeping safe and the national strategy by considering community safety priorities and needs in Kelantan’s flood disaster communities including communication, cooperative approaches; maximizes the opportunity to compare and add the previous study finding and lastly it will aligns with international activities. Study significance & Conclusion: The successfully used of standardized resilience scorecard and resilient tool will indicate the increased quality, quantity and capability of the government, healthcare and emergency preparedness team across Malaysia and it enable necessary reallocations of aid thus allowing communities to become more resilient, less aid required needed for prevention, response and recovery.